BIOLOGICALLY ACTIVE SUBSTANCES OF HIBISCUS SABDARIFFA L. EXTRACTS AS COMPONENTS OF LOTION WITH ANTI-INFLAMMATORY AND ANTIOXIDANT EFFECTS - Александрова, Олександра; Бачуріна, Марія (SWorldJournal, 2026)
The experimental study is devoted to studying the influence of extraction conditions on the content of anthocyanins and polyphenolic compounds in extracts from Hibiscus Sabdariffa flowers. It was found that the optimal extractant for anthocyanins and pol